Advanced quality auditing : an auditor's review of risk management, lean improvement, and data analysis - Coleman, Lance B., Sr., 1962- (American Society for Quality, Quality Press, 2015)
Auditors from any industry must "learn the language of upper management" if they truly want to effect positive change throughout their environments. If quality auditors want to remain relevant and keep from becoming marginalized, they need to add new skills and credentials, and even more importantly, move beyond conformance monitoring to determine how their work might impact the corporate bottom line. The purpose of this book is to accept that challenge in presenting two ways that auditors can "learn [to speak] the language of upper management", either by helping to drive continuous improvement or by helping to manage risk. This book has essential information that will help guide an organization's efforts to glean more value from their audit process. It helps grow the audit function beyond verification audits. It provides insight for using the audit function to improve organizations using lean principles. It also discusses how the audit function can contribute to and be formally integrated into the ongoing risk management program. This book is about advancing the profession of auditing, as well as the skills of individual auditors.